E-050 First-Line Treatment by Embolization with Intention-to-Cure in the Management of Cranial Dural Arteriovenous Fistulas. (29th July 2016) - Cord, B; Sommaruga, S; Yeung, J; Johnson, M; Matouk, C
Abstract : Introduction/purpose: Cranial dural arteriovenous fistulas (dAVFs) represent abnormal arteriovenous shunts supplied by dural arteries. Their natural history and presentation depend on the pattern of venous drainage encapsulated in the Borden classification. When cortical venous reflux (CVR) is present, aggressive management is mandated. The treatment of cranial dAVFs lacking CVR may be warranted. Treatment modalities include surgical disconnection, radiosurgery, and embolization (alone or in combination). Here we report our early experience in the management of cranial dAVFs using a philosophy of first-line embolization with intention-to-cure. Materials and methods: A series of consecutive cranial dAVFs ( n = 14) treated by a single operator (CM) at Yale-New Haven Hospital (November 2011 – March 2016) were analyzed. The mean age at presentation was 61 ± 12 years (57% male). The locations of cranial dAVFs included transverse sinus ( n = 6), cavernous sinus ( n = 2), anterior skull base ( n = 2), straight sinus ( n = 2), hypoglossal canal ( n = 1), and midline cerebellar ( n = 1). Borden types included I ( n = 1), II ( n = 3), and III ( n = 10). Borden types II/III lesions presented most commonly with venous congestion±hemorrhage (80%). A trans-venous approach was prioritized as a first-line treatment strategy. When a trans-venous approach was not possible, as in a majority of type III lesions (80%), a trans-arterial embolization was performed with intention-to-cure, i.e., penetration of liquid embolic into the draining vein. Mean angiographic and clinical follow-up were 12.4 ± 12.2 months (median = 7.1 months, range = 2.1–40.1 months) and 19.4 ± 15.4 months (median = 13.7 months, range = 2.1–44.7 months), respectively. Cure was defined as elimination of CVR on follow-up imaging. Results: The overall cure rate of cranial dAVFs treated using a first-line embolization with intention-to-cure philosophy was 71.4%. Three patients required an additional treatment modality (2 Gamma Knife radiosurgery and 1 open surgery) resulting in an overall cure rate of 92.6%. A single, elderly patient who presented with a cerebellar hemorrhage died 10 days after a partial trans-arterial embolization due to the severity of her initial hemorrhage. First-line trans-venous embolization resulted in an overall higher embolization-only cure rate (86%) compared to first-line trans-arterial embolization (57%). Both approaches were associated with low permanent morbidity (overall 7.1%) however the trans-venous approach was fraught with more frequent technical complications, e.g., coil migration. Of note, a single case of trans-venous embolization of a Borden type II transverse sinus dAVF was associated with conversion to a type III lesion complicated by a small, delayed intraparenchymal hemorrhage and new visual field deficit from which the patient completely recovered. Her residual dAVF spontaneously thrombosed resulting in a durable cure. Conclusions: A philosophy of first-line embolization with intention-to-cure of cranial dAVFs is both safe and effective with low morbidity and high, durable cure rates. When possible, a trans-venous route is preferred with higher chances of immediate cure using embolization as a standalone therapy. Disclosures: B. Cord: None. S. Sommaruga: None. J. Yeung: None. M. Johnson: None. C. Matouk: None.